A Unified Model for Addressing Hunger in Developed Countries: An Evidence-Based Analysis Integrating Climate Challenges, Country Stability, Economic Structures, and Policy Effectiveness - Reuveni, Saada (Technium Social Sciences Journal, 2025)
Hunger and food insecurity persist in developed countries, even amid wealth and abundant food resources, due to complex interconnections between climate challenges, political stability, economic inequality, and policy effectiveness. This paper introduces a unified model that integrates these four indicators to address food insecurity within affluent societies. Through an analysis of data from 20 developed nations and in-depth case studies of ten, we explore how these factors correlate with hunger rates. The results indicate that a multi-dimensional approach is essential for effectively reducing hunger. Specifically, countries that implement climate-resilient strategies, maintain political stability, promote economic equity, and apply targeted policies demonstrate significantly lower rates of food insecurity. Notably, the findings reveal that income inequality and climate resilience are critical drivers of food access disparities, while social spending alone may not suffice without strategic targeting. This study highlights the importance of a comprehensive, context-specific framework for addressing food insecurity, offering actionable recommendations for policymakers and stakeholders. By fostering climate adaptation, ensuring stable governance, and prioritizing equity in social programs, developed countries can more effectively combat hunger and support sustainable food security for all.